UJI IN VITRO EFEKTIVITAS DAUN NANGKA (Artocarpus heterophyllus) TERHADAP MORTALITAS CACING - Mustabi, Jamila; Yulianti, Farida (Jurnal Nutrisi Ternak Tropis dan Ilmu Pakan, 2025)
Jackfruit leaves can be an alternative feed during the dry season and become anthelmintic because they contain tannins that can prevent the development and kill worms in livestock. This study aims to evaluate vitro the mortality of worms in the administration of jackfruit leaves. This study consisted of six treatments and four replicates, using statistical analysis of Complete Random Design, namely:   the addition of P0: NaCl 0.9; P1: albendazole; P2:10% jackfruit leaf extract (EDN); P3: 25% EDN; P4: 50% EDN and P5: 100% EDN. The study showed that adding jackfruit leaves had a real effect (P<0.01) on worm death. The number of worm deaths in the second hour was no different between the administration of 25% (P3) and 50% (P4) EDN, but it was different from the administration of 100% EDN (R5), while at the 3rd hour, there was no significant difference between the treatment of 50% (P4) and 100% (P5). In conclusion, a concentration of 100% EDN at the 3rd hour killed 100% of the worms Haemonchus contortus